The "Skin Cap" story goes on. - Cutrone, M. (European Journal of Pediatric Dermatology, 1997)
In a previous report on this Journal we described the sudden rise and fall of "Skin Cap", from the very important clinical and commercial success to its withdrawal imposed by FDA on August 7, 1997. "Skin Cap" is an antipsoriatic counter product coming from Spain (Cheminova International, Madrid) officially consisting only of zinc pyrithione but really illegally charged with clobetasol 17-proprionate (...).